Step-Wise Extraction of Metals from Dredged Marine Sediments - Yoo, Jong-Chan; Kim, Eun-Jung; Yang, Jung-Seok; Baek, Kitae (TAYLOR & FRANCIS INC, 2015)
In this study, step-wise extraction using various extracting agents was carried out in order to enhance the removal of metals from contaminated dredged marine sediment. Five-times repeated extraction using HCl could extract approximately 23% of the As from the sediment, while NaOH extracted 14% of the As with a single extraction. An alternate application of EDTA and HCl extracted 17%, 34%, 9%, 87%, and 41% of the Cd, Cu, Ni, Pb, and Zn, respectively. Step-wise extraction reduced the risk index (RI) of heavy metals to 49% compared with untreated sediments, which were caused mainly from the decrease in the Cd concentration after chemical extraction in sediment.
Keywords: ECOLOGICAL RISK-ASSESSMENT; SEQUENTIAL EXTRACTION; CONTAMINATED SOIL; HEAVY-METALS; HARBOR SEDIMENTS; REMEDIATION; ACID; EDTA; ZN; PB